2017
DOI: 10.1002/mame.201600481
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration Membranes Functionalized with Polydopamine with Enhanced Contaminant Removal by Adsorption

Abstract: The performance of polymeric ultrafiltration membranes functionalized with polydopamine to couple depth adsorption of contaminants with the typical surface rejection characteristics of the membrane is investigated. Two approaches are deployed to achieve this functionalization: in a two‐step method, the ultrafiltration membranes are initially fabricated by phase inversion, then followed by coating with polydopamine; in a more facile and advantageous one‐step method, the membranes are subjected to phase inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…For example, it has been demonstrated that the PD deposition on polysulfone membranes increased the removal of a representative positively charged contaminant as methylene blue (MB) with increasing PD coating time. 23 The increased removal of heavy metals and metal cations (i.e., Cd(II) and Pb(II)) upon PD functionalization of graphene hydrogel was also reported. 24 A similar behavior was also observed for PD-functionalized zeolite that showed an adsorption capacity toward Cu(II) at pH = 5.5, about 40% higher than that of the pristine material.…”
Section: Introductionmentioning
confidence: 90%
“…For example, it has been demonstrated that the PD deposition on polysulfone membranes increased the removal of a representative positively charged contaminant as methylene blue (MB) with increasing PD coating time. 23 The increased removal of heavy metals and metal cations (i.e., Cd(II) and Pb(II)) upon PD functionalization of graphene hydrogel was also reported. 24 A similar behavior was also observed for PD-functionalized zeolite that showed an adsorption capacity toward Cu(II) at pH = 5.5, about 40% higher than that of the pristine material.…”
Section: Introductionmentioning
confidence: 90%
“…Membrane‐based techniques have received much attention in the field of micropollutants removal due to their convenient and continuous operation . But the traditional membranes separated micropollutants mainly by means of the size exclusion effect or charge effect, and it may not work for some small molecular organic micropollutants with electric neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument is equipped with an ATR accessory containing a diamond crystal internal reflection element. The analysis was carried out with a resolution of 4 cm -1 and samples were scanned 32 times in the wavenumber range between 750 and 3750 cm -1 [29]. Thermogravimetric analyses (TGA) were performed with a Mettler TGA/SDTA 851 instrument between 20 and 650 °C at a heating rate of 10 °C min −1 in air.…”
Section: Characterization Of Supports and Membranesmentioning
confidence: 99%
“…The surface and cross-sectional morphology of the membranes was analyzed through field emission scanning electron microscopy (FESEM). The instrument is the MERLIN model by ZEISS, equipped with a state-of-the-art GEMINILIS column, to ensure accurate control of spot and current [29]. The operational voltage was 5kV, except for the samples fabricated following 6.5 reaction cycles, for which the voltage was adjusted to 7.5 kV.…”
Section: Characterization Of Supports and Membranesmentioning
confidence: 99%